The Influence of Corporate Governance on Potential Financial Distress on Transportation Companies listed on the Indonesia Stock Exchange for the period 2013-2017 - Elisabeth Juliana Lelu; Hakiman Thamrin (Syntax Corporation Indonesia, 2021)
This study aims to empirically examine the effect of characteristics corporate governance (managerial ownership, institutional ownership, board of commissioners, independent commissioners, board of commissioners, audit committee) on financial distress. This study uses data collection methods using the method of library research. In this study the type of secondary data used is in the form of financial statements from transportation companies listed on the Indonesia Stock Exchange in the period 2013-2017. Research data is data that is presented in time series. Data analysis was performed through descriptive statistical tests, followed by testing the feasibility of the regression model, testing the overall Fit Test model, the coefficient of determination test, and the classification matrix. Logistic regression analysis is used because the dependent variable used in this study is a dummy variable, which is a company with the possibility of financial distress. The results of this study indicate that: Managerial ownership has a significant effect on financial distress, Institutional ownership is proven to have a significant influence on financial distress, the Board of Commissioners is proven to have a significant influence on financial distress, independent commissioners is proven to have a significant influence on financial distress, The board of directors is proven to have a significant influence on financial distress and the Audit Committee is proven to have a significant effect on financial distress